Web links as research indicators: analogues of citations? Web links, Citation study, Research measurement, Motivation - Alastair G Smith (Information Research: An International Electronic Journal)
This exploratory study investigates the extent to which web links are analogues to the citations in traditional print literature. A classification of links is developed, using the nature of source and target pages, and the reason for linking. Links to a sample of research oriented websites (universities, professional institutes, research institutes, electronic journals, and individual researchers) were classified. Overall, 20% of the links in the study could be regarded as research links analagous to citations.